Superparamagnetism and ferrimagnetism in the Sr2FeMoO6–δ nanoscale powder. Issue 16 (15th August 2022) - Kalanda, Nikolay; Yarmolich, Marta; Burko, Alexander; Temirov, Aleksandr; Kislyuk, Aleksandr; Demyanov, Sergey; Lenz, Kilian; Lindner, Jürgen; Kim, Dong-Hyun
Abstract: Using combined synthesis modes and optimized conditions for ultrasonic dispersion, we obtained a single-phase nanosized Sr2 FeMoO6–δ powder having a high degree of superstructural ordering of Fe and Mo cations (88 %) and an average grain size of 70.8 nm. The results of the Mössbauer spectroscopy and magnetic measurements show that the obtained nanosized strontium ferromolybdate powder is in a magnetically inhomogeneous state, consisting of superparamagnetic and ferrimagnetic phases. In comparison with the superparamagnetic component of magnetization, the ferrimagnetic component has higher values and rises smoothly until reaching saturation as the temperature decreases. Showing that there is no exchange magnetic interaction between the grains in the superparamagnetic phase, allowed us to estimate the critical sizes, of nanoparticles, d spm, in the single-domain state using the Néel-Brown model. The obtained value of d spm is smaller than the size of the single-domain particles, which confirms the absence of the frozen state in some of the superparamagnetic particles. These results are important for understanding the effects of nanosized grains on the magnetic properties and features of magnetization of the Sr2 FeMoO6–δ polydisperse powder, a promising material for spintronic device applications.